2020
DOI: 10.15405/epsbs.2020.08.98
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Creativity: Cognitive And Communicative Aspects

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…It also involves contextually relating to the social situation, cultural background, and other personal aspects unique to individuals. Advertisements must align with these aspects to be effective, as confirmed by both prior studies and various other research in advertising (Arora & Jain, 2021;Girsang, 2015;Joy et al, 2009;Kshenovskaya, 2017;Perić & Jevtović, 2022;Xu & Liu, 2022). For instance, an advertisement saying "Discover the 1000 temples" could be broken down into a conceptual blending diagram as follows: The themes from the phrase "Discover the 1000 Temples" within a generic space that shares similar elements are "vacation" and "religious belief."…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It also involves contextually relating to the social situation, cultural background, and other personal aspects unique to individuals. Advertisements must align with these aspects to be effective, as confirmed by both prior studies and various other research in advertising (Arora & Jain, 2021;Girsang, 2015;Joy et al, 2009;Kshenovskaya, 2017;Perić & Jevtović, 2022;Xu & Liu, 2022). For instance, an advertisement saying "Discover the 1000 temples" could be broken down into a conceptual blending diagram as follows: The themes from the phrase "Discover the 1000 Temples" within a generic space that shares similar elements are "vacation" and "religious belief."…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, the persuasive effectiveness of an advertisement is significantly impacted by the application of complex interpretations, such as the use of imagery functions for commercialization and a substantial degree of crosscultural understanding to present the product to a broad audience. Kshenovskaya (2017), examined the role of humor in advertisements by employing conceptual blending theory. The study found that humor enhances the advertisement's attractiveness, thereby raising consumer interest in purchasing or subscribing to products.…”
Section: Introductionmentioning
confidence: 99%